Mathematical model exchange of weight of processes in tanks of the plane - Бойченко, С. В.; Федорович, Л. А. (Proceedings of National Aviation University (archive), 2021)
It is analysed exchange of weight processes which occur in fuel tanks of the plane during flight. The mathematical model which describes these processes is constructed.